THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE RELATIONSHIP BETWEEN SERVICE QUALITY AND LOYALTY: AT MOKOPI GARDEN - Ismail, Dede; Nisa, Alifia Khairun; Adhadiana, Elysa Fitria; Anakota, Reflita; Susilawati Sugiana, Neng Susi (Jurnal Komputer Bisnis, 2025)
— This study aims to investigate the role of customer satisfaction as a mediating variable in the relationship between service quality and customer loyalty at Mokopi Garden, a growing coffee shop located in Bandung. As competition in the culinary business intensifies, understanding how service quality drives loyalty through customer satisfaction becomes crucial. This research adopts a quantitative approach with a sample of 50 respondents who are regular visitors of Mokopi Garden. Data were collected using a structured questionnaire based on indicators of service quality, customer satisfaction, and loyalty. The collected data were analyzed using SPSS version 26, including regression and mediation analysis (Sobel test) to examine the indirect effect of service quality on loyalty through satisfaction. The findings indicate that service quality has a significant and positive impact on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction partially mediates the relationship between service quality and loyalty. This suggests that while service quality directly influences loyalty, its effect is enhanced when customers are satisfied with the services provided. These results emphasize the importance for Mokopi Garden to consistently deliver high-quality service in order to foster satisfaction and build long-term loyalty among its customers. Practically, this research provides valuable insights for coffee shop managers and marketers to prioritize service improvements as a strategic tool to enhance customer satisfaction and loyalty. The uniqueness of this study lies in its specific focus on a local brand within a competitive urban market, offering contextual relevance and actionable recommendations.